Can linear transportation infrastructure verges constitute a habitat and/or a corridor for biodiversity in temperate landscapes? A systematic review protocol. Issue 1 (December 2016) - Jeusset, Arzhvaël; Vargac, Marianne; Bertheau, Yves; Coulon, Aurélie; Deniaud, Nadine; Flamerie De Lachapelle, Frédérique; Jaslier, Emmanuel; Livoreil, Barbara; Roy, Véronique; Touroult, Julien; Vanpeene, Sylvie; Witté, Isabelle; et al.
Abstract Background The role of linear transportation infrastructures (roads, railways, oil and gas pipelines, power lines, rivers and canals) in fragmenting natural habitats has been demonstrated. Yet, the potential of habitat or corridor of their verges (road and railway embankments, strips of grass under power lines or above buried pipelines, or waterway banks) for biodiversity remains controversial. In a context of decreasing natural habitats, the potential of anthropogenic areas for contributing to wildlife conservation should be considered. Moreover, how linear transportation infrastructure verges should be managed in order to favor biodiversity is a crucial question. The present work describes the protocol of the first systematic synthesis of evidence of the potential of linear transportation infrastructure verges as habitat and/or corridor for biodiversity. Outcomes of the study will be useful for helping managers to improve their practices or for prioritizing actions of ecological restoration. Methods The subject population will include both flora and fauna of the temperate climate, either species or communities. Exposures to linear transportation infrastructure verges, interventions of verge management (mowing, pruning, etc.) and environmental disturbances (pollution, wildfires, etc.) will be included. Both temporal and spatial comparators will be considered. Relevant outcomes will include dispersal, species richness and abundance. The scientific literature on the topic of the review may turn out to be very heterogeneous. Various management types, biodiversity outcomes and study designs might be conceived. If any combination of these is covered by a sufficient number of studies, we will perform a meta-analysis. At the least, we will produce a systematic map and a narrative synthesis.